Sustainable Urban Transport and the Level of Road Noise ‑ a Case Study of the City of Bydgoszcz - Szopińska, Kinga (Geomatics and Environmental Engineering, 2019)
Road transport in cities is one of the main sources of air and noise pollution, lowering the attractiveness of areas of sensitivity, influencing the quality of life and the ability to meet the basic needs of users. The reconstruction of the existing road network and introduction of a new, alternative type of transport can radically change the acoustic conditions occurring in a city. As a result of this, an assessment of the noise nuisance of a fragment of the city of Bydgoszcz ‑ a city located in the northern part of Poland ‑ which had undergone changes connected with transportation, was carried out in the work. The influence of a newly-built tram route "œBydgoszcz-Fordon" on the acoustic conditions occurring in its surroundings was assessed. The studies were carried out in two periods of time (2012 and 2019), corresponding to various spatial states of the terrain. The results confirm that the introduction of an alternative transport solution contributed to a decrease in the level of road traffic noise. This occurs as a result of improved road conditions on modernized road segments, the integration of transportation networks and a decrease in the share of individual road vehicle transport. It was also confirmed that a well-designed tram route can influence changes in transportation habits of users and have a positive effect on the attractiveness of residential areas. This is in line with the concept of sustainable urban transport.